Diet modulation of the microbiome of the pest storage mite Tyrophagus putrescentiae - Hubert, Jan; Nesvorna, Marta; Sopko, Bruno; Green, Stefan J (FEMS microbiology ecology, 2023)
Storage mites colonize a wide spectrum of food commodities and adaptations to diets have been suggested as mechanisms enabling successful colonization. We characterized the response of seven unique Tyrophagus putrescentiae cultures (5K, 5L, 5N, 5P, 5Pi, 5S, and 5Tk) with different baseline microbiomes to different diets. The offered diets included a rearing diet, protein-enriched diet, oat flakes, and sunflower seeds. Microbiome characterization was performed using 16S ribosomal RNA (rRNA) gene amplicon sequencing and 16S rRNA gene quantitative PCR. The mite culture microbiomes were classified into four groups: (i) Sodalis-dominated (5Pi), (ii) Wolbachia-dominated (5N and 5P), (iii) Cardinium-dominated (5L and 5S), and (iv) asymbiontic (5K and 5Tk) mites dominated by Bacillus and Bartonella. Mite growth rates were most strongly affected by nutrients in the diet, while respiration and microbial community profiles were largely influenced by mite culture. While growth rate was not directly explained by microbiome composition, microbiomes strongly influenced mite fitness as measured by respiration. While diet significantly influenced microbial profiles in all cultures, the effect of diet differed in impact between cultures (5Pi > 5S > 5N > 5K > 5Tk > 5L > 5P). Furthermore, no new bacterial taxa were acquired by mites after dietary changes. Bacteria from the taxa Bacillus, Bartonella-like, Solitalea-like, Kocuria, and Sodalis-like contributed most strongly to differentiating mite-associated microbiomes.
Keywords: Acaridae; RNA, Ribosomal, 16S; diets; Mites; dieta; Bacteria; roztoči; Bacteroidetes; Microbiota; mikrobiota; Enterobacteriaceae; RNA ribozomální 16S; zvířata; fitness; transmission; Diet; microorganisms; feeding; mite; Animals